Effect of Impactor Design on Unidirectional and Woven fiber Reinforced Composites - Ahmed, Payman Sahbah (Sulaimani Journal for Engineering Sciences, 2016)
Since impact damage resistance is such an important property for composite materials, this research is devoted to study the effect of impactor design on the impact properties of epoxy composites reinforced with unidirectional glass, unidirectional carbon, woven glass and hybrid woven (glass + carbon) fibers . This research shows changing the impactor design have no effect on impact properties of woven reinforced composites while it has a significant effect on unidirectional fiber reinforced composites, impact damage behavior of woven composites is in the form of indentation and perforation while the behavior is matrix cracking and splits along the fiber direction and fracture for unidirectional fiber reinforced composites under impact loading and finally Glass fiber reinforced composites have a better impact properties than carbon reinforced composites.
Keywords: drop weight impact; impactor design; unidirectional fiber composites; woven fiber composites